RETRACTION: Comparative Study of Green Accounting Implementation Based on University Social Responsibility (Csr) and Good University Governance (Gug) Policy - Dwi Suhartini; Astrini Aning Widoretno; Rizdina Azmiyanti (Basic and Applied Accounting Research Journal, 2021)
This study aims to examine a comparative study of the implementation of green accounting based on USR as the application of GUG in universities in Indonesia. USR-based green accounting has 4 dimensions, namely environmental awareness, environmental involvement, environmental reporting, and environmental auditing. However, the implementation of USR-based green accounting has not been implemented properly, especially in the environmental reporting and auditing dimensions, while awareness and involvement in environmental activities have been implemented very well. The research method uses a literature review of journal articles with relevant topics. The results of the study prove that environmental awareness and environmental involvement have been implemented very well by State Universities and Private universities in Indonesia, while environmental reporting and environmental audit have not been carried out optimally. For this reason, the implementation of GUG has not been implemented properly. The regulations governing USR have not yet been established and the environmental audit function has not received maximum attention. The environmental audit function is not included in the SPI's duties, because the SPI's task functions only focus on the management and implementation of controlling financial resources, human resources, and also facilities and infrastructure resources.